2015
DOI: 10.3126/jcmc.v5i1.12568
|View full text |Cite
|
Sign up to set email alerts
|

Level of depression among elderly in selected old age homes at Mangalore, India

Abstract: Maternity incentive schemes were to encourage mothers to use skilled birth attendance for the best prevention of maternal and child death where as the pregnant women should have access to high quality prenatal care which, they can afford and where, they are treated with respect. The objective of the study was to determine the knowledge and utilization of maternal incentives scheme on delivery services at rural area of Nepal. This study was cross-sectional descriptive in nature and Study was conducted in Panchk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
2
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
3
2
0
Order By: Relevance
“…12 Present study showed a significant association between level of depression and marital status of respondents (p=0.00001). This finding is similar to that of the study by Subba et al (p=0.019), 18 Sangma et al(p=0.0001) 19 and Thilak et al(p=0.0001). 20 Studies have shown that unmarried, divorced and widow/widower respondents are more likely to have depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…12 Present study showed a significant association between level of depression and marital status of respondents (p=0.00001). This finding is similar to that of the study by Subba et al (p=0.019), 18 Sangma et al(p=0.0001) 19 and Thilak et al(p=0.0001). 20 Studies have shown that unmarried, divorced and widow/widower respondents are more likely to have depressive symptoms.…”
Section: Discussionsupporting
confidence: 92%
“…14 This study shows that age of elderly people matters for depression which is supported by the study of previous epidemiological study 14 and in contradiction of the study in india. 15 The proportion of female who were suffered with high degree of depression is higher than the male which is also statistically significant and the result is similar to the studiesdone in India. 6,16,7 This means females are more likely to have more depressed.…”
Section: Discussionsupporting
confidence: 83%
“…Demographic findings of the study revealed that nearly half of the respondents (48%) belonged to the age group 70-79 years which is consistent with the study done in Mangalore, India where (48%) belonged to the same age group. [8] With regards to the gender, more than half of the respondents 73.1% were female, similar to the study done in West Bengal, India, where 67.08% of total respondents were female. [9] Regarding length of stay in geriatric home, 57.7% of the respondents lived in the old age home for more than one year which is consistent with the study of Narkhede V. et al…”
Section: Discussionsupporting
confidence: 76%